Investigation and production of non-cytotoxic TixNbxSn (x = 5,10,15,20) alloys by high-energy mechanical milling with antibacterial activity - Batibay, A. B.; Erci, F.; Kotan, H.; Karavelioglu, Z.; Koc, R. Cakir; Oral, I.; Evcin, A. (ELSEVIER, 2023)
In this research, TixNbxSn (x = 5, 10, 15, 20 wt%) alloys were produced by high-energy mechanical alloying, and their potential applications as biomaterial were investigated through the microstructural characterizations (via XRD, SEM, and EDS analyses), mechanical tests (via hardness and elastic modulus tests), and biological studies (via antibacterial and cytotoxic tests). The alloying studies were carried out at room temperature in a highenergy ball milling for 8 h followed by a consolidation using a uniaxial pressing and 2 h pressureless sintering at 1150 degrees C. The XRD and EDS analyses showed that & alpha;-Ti, & beta;-Ti, and TiC phases were present in the microstructure after sintering at high-temperature. Hardness tests revealed a wide range of values between 384 and 723 HV depending on the alloy compositions. That is, the volume fraction of TiC phase formed during processing and the ratio of & alpha;-Ti/& beta;-Ti phases appear to control the hardness of the alloys. The elastic modulus was determined ranging from 70 to 103 GPa as a function of compositions with Ti15Nb15Sn alloy having the closest elastic modulus to the bone. The biological investigations revealed that TiNbSn alloys exhibited antibacterial properties against Staphylococcus aureus (S. aureus) and were not cytotoxic to healthy cells, regardless of their compositions. Furthermore, the findings indicated that when the cells were subjected to various dilutions of alloy extracts, there was a noticeable enhancement in both cell proliferation and viability. These findings have the potential to pave the way for novel approaches in the creation of TiNbSn alloys as biomaterials.
Keywords: Mechanical milling; Titanium alloys; Biomaterials; Elastic modulus; Cytotoxicity; Antibacterial activity; SN-NB ALLOY; TITANIUM-ALLOYS; IMPLANTS; MICROSTRUCTURE; CORROSION; Materials Science